Penerapan Metode Sosiodrama Tema Berbuat Baik Kepada Kedua Orang Tua Untuk Meningkatkan Hasil Belajar Siswa: Indonesia - Nikmah; Syahri Ramadhan; Nofita Tryana; Nelia Guswanti (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2019)
The method of sociodrama is seen as being able to dramatize behavior with the theme of doing good to both parents. so that it can be ingrained in the learner through habituation in everydaylife. This research is a Class Action (PTK) research consisting of two cycles. The problem of this research is the low learning outcomes of grade III students at MI Al-Kifayah Pekanbaru. Therefore, researchers are trying to improve student learning outcomes by using sosiodrama method as a method that can improve student learning outcomes with the theme of doing good to both parents. Data collection tools using Observation and written tests. From the results of this study showed an increase by using the method of sosiodrama as a method of learning in the class. This can be seen from the increase in cycle 1 to 76%. in the second cycle of meeting II teacher activities reached 93% so there was an increase of 19%. Student activity in cycle 1 reached 74% in the second cycle of student activities reached 90%. So there was an increase of 17%. While student learning outcomes in the first cycle reached 70% and in the second cycle 87% there was an increase of 17%. From these results, it can be concluded that the implementation of sosiodrama method as a learning method influences the learning outcomes of class III students of MI Al-Kifayah Pekanbaru.